In vivo intraoperative hypoglossal nerve stimulation for quantitative tongue motion analysis. Issue 6 (2nd November 2017) - van Alphen, M.J.A.; Eskes, M.; Smeele, L.E.; Balm, A.J.M.; van der Heijden, F.
Abstract Abstract : This is the first study quantitatively measuring tongue motion in 3D after in vivo intraoperative neurostimulation of the hypoglossal nerve and its branches during a neck dissection procedure. Firstly, this study is performed to show whether this set-up is suitable for innervating different muscles or muscle groups with an identifiable corresponding motion pattern by stimulating the main stem and the visible branches and by performing an intra-patient comparison over the captured 3D trajectories. Secondly, an inter-patient comparison is performed to analyse if similar branches lead to comparable movements of the tongue tip. Our results showed the measurement set-up works, and that we are able to capture distinguishable trajectories for different branches. The inter-patient comparison showed a poor match in trajectories for similar branches, which could be an indication of the presence of several anatomical variations between individuals.